Intergenerational wealth transmission in Great Britain - Paul Gregg; Ricky Kanabar (University of Essex, Institute for Social and Economic Research (ISER), 2021)
We document the intergenerational persistence of wealth between adult offspring and their parent's using the Wealth and Assets Survey for Great Britain. We estimate an intergenerational wealth elasticity of 0.4 and rank-rank elasticity of 0.3 and find wealth persistence for individuals in their 60s is lower than for those currently aged in their 30s and early 40s, though rank based estimates are stable. We estimate that the intergenerational wealth elasticity is 3.8 percentage points higher when comparing people with those the same age six years previously suggesting strong evidence of higher intergenerational wealth persistence in younger age cohorts.
Keywords: D31; D63; I24; 330; Wealth; Inequality; intergenerational mobility; Great Britain